Strengthening Mental Health Literacy and Awareness Among Adolescents Through a Technology-Based Educational Approach : Penguatan Literasi dan Kesadaran Kesehatan Mental Remaja Melalui Pendekatan Edukatif Berbasis Teknologi - Sardiana, Anna (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2025)
Mental health is an increasingly critical issue among Generation Z, particularly due to rising academic and social pressures faced by adolescents. This community service program aimed to improve students’ mental health literacy through digital-based education utilizing the Psy-Share platform. The program was conducted at SMAN 93 Jakarta, involving direct health education and the distribution of a Google Form to map students’ psychological conditions and assess their need for online mental health services. Evaluation results showed that 95.8% of respondents agreed with the formal launch of Psy-Share, indicating a high level of acceptance toward digital and innovative educational approaches. However, the development process of this platform encountered challenges, particularly in brand building and addressing stigma surrounding online mental health services. In response, the implementing team developed a robust branding strategy and emphasized educational public communication supported by user testimonials. This program demonstrates that digital approaches can be effective tools in promoting mental health education among adolescents and expanding access to inclusive, responsive mental health services tailored to Generation Z's needs.